SIMILARITIES AND DIFFERENCES OF GENDER IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - TO‘XTAMURODOVA NILUFAR (TADQIQOTLAR.UZ, 2024)
This study examines the ways in which the concept of grammatical gender is expressed in the English and Uzbek languages. While English is considered a gender- neutral language, Uzbek has a grammatical gender system with masculine and feminine forms. The analysis compares how nouns, pronouns, and adjectives are marked for gender in each language. In Uzbek, nouns are classified as either masculine or feminine, and this gender agreement extends to associated pronouns and adjectives. In contrast, English does not have a grammatical gender system, though certain natural gender distinctions are maintained in personal pronouns.The paper also explores how the presence or absence of grammatical gender impacts other linguistic features, such as the formation of compound words and the use of gender-specific honorifics. Additionally, it discusses the sociocultural implications of gender representation in the grammar of these languages.Through a contrastive analysis, this study sheds light on the diverse ways in which human languages can encode and express the concept of gender, highlighting both universal patterns and language-specific variations in this domain of grammar.